Hysterosalpingographic Evaluation of Uterus and Fallopian Tubes of Infertile Women (Journal of Nobel Medical College, 2017)
Background: Hysterosalpingography (HSG) is a routinely performed radiological investigation for evaluation of uterine cavity morphology and fallopian tube patency in infertile women. This study was undertaken to describe patterns of HSG findings and to assess any significant difference in uterine and fallopian tube findings in women with primary and secondary infertility in eastern part of Nepal.Material and Methods: Hospital based cross sectional descriptive study was conducted by retrospectively analyzing HSG records of 216 infertile women (both primary and secondary infertility) done from April 2014 to August 2016. Radiological findings in uterus and fallopian tubes were recorded and analyzed. Association between two categorical variables was examined by Chi-square test.Results: Majority of infertile women (53.2%) had primary infertility. Abnormal HSG was seen in 44.9% infertile women and higher in secondary infertility (57.4%) than with primary infertility (33.9%) (OR = 2.63, 95% CI = 1.51 – 4.57, P value = 0.001). Tubal abnormality was common than uterine abnormality (36.1% versus 8.8%, P value= 0.001). Tubal abnormalities were higher in women with secondary infertility than with primary infertility (52.5% versus 21.7%), whereas uterine abnormalities were common with primary infertility compared to secondary infertility (12.2% versus 5.0%) (P value= 0.001).Conclusion: Abnormal HSG was more associated with secondary infertility. Infertility was significantly associated with tubal abnormality than with uterine abnormality. Tubal abnormalities are common in women with secondary infertility whereas uterine abnormalities are common in women with primary infertility and are statistically significant.Journal of Nobel Medical CollegeVolume 6, Number 1, Issue 10 (January-June, 2017), Page: 63-71